2018
DOI: 10.1093/heapro/day018
|View full text |Cite
|
Sign up to set email alerts
|

Social media and health information sharing among Australian Indigenous people

Abstract: Despite the enormous potential of social media for health promotion, there is an inadequate evidence base for how they can be used effectively to influence behaviour. In Australia, research suggests social media use is higher among Aboriginal and Torres Strait Islander people than the general Australian population; however, health promoters need a better understanding of who uses technologies, how and why. This qualitative study investigates what types of health content are being shared among Aboriginal and To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…Young mothers may also be responsive to social media messages that alert them to the risks of skin infections in their new babies and how to seek care. 26 Higher rates of hospitalisation with skin infection in boys compared with girls are consistent with findings from New…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Young mothers may also be responsive to social media messages that alert them to the risks of skin infections in their new babies and how to seek care. 26 Higher rates of hospitalisation with skin infection in boys compared with girls are consistent with findings from New…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, given our finding of this risk factor there might be a benefit in educating health care workers about the need for additional health care assessments for infants of young mothers, to detect and treat skin infections early. Young mothers may also be responsive to social media messages that alert them to the risks of skin infections in their new babies and how to seek care …”
Section: Commentmentioning
confidence: 99%
“…However, the authors acknowledge that their findings highlight the potential vehicle of social media to have conversations that promote change [9]. In addition, a recent study has found that Australian Aboriginal people interact about their health using social media [27]. Our review highlighted that research that addresses and evaluates decolonization and self-empowerment will be more likely to improve Aboriginal health outcomes [11,20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the general community and those in financial hardship, Aboriginal respondents with higher social media usage were less likely to indicate post-flood distress and PTSD, perhaps because it increases social connectedness in this group. Previous research has shown social media use to be more common among Aboriginal compared to non-Indigenous people [ 55 ]. There is complexity in the relationship between the use of technology and social connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…Social media can be an effective tool if used to strengthen existing relationships or initiate new meaningful ones (rather than as a substitute for real-life interaction) [ 57 ]. It may also be an effective vehicle for managing disaster risk and providing health messaging and education [ 55 , 58 ].…”
Section: Discussionmentioning
confidence: 99%